Research on Axial Compression Test and Finite Element Analysis of Sea Sand Concrete Filled CFRP-Steel-CFRP Composite Circular Tubular Stub Column - Peng, Guihan; Yu, Liqiong; Yao, Baomin; Luo, Huiling (Transactions on Engineering and Technology Research, 2024)
In order to study axial pressure performance of sea sand concrete filled CFRP-steel-CFRP composite circular tubular stub column, the finite element model of composite constrained short column was established by using ABAQUS, based on experimental research. The accuracy of the finite element model was validated by comparing the finite element with the experimental data. Furthermore, the influence of the number of CFRP layers, the tensile strength of CFRP and the thickness of steel tube on the mechanical properties of components was explored. Finally, the applicability of the existing algorithms for bearing capacity was discussed and a simplified calculation formula was proposed. The results indicate that the structural parameters are directly proportional to the bearing capacity of the components, and the increase of CFRP layers is the most significant. With the increase of CFRP layers, the stiffness of the linear strengthening section of load-displacement curve can also be significantly improved. The existing relevant bearing capacity algorithms are relatively conservative for the combined structure, and the simplified calculation formula presented in this paper has little deviation from the experimental value.